American College of Clinical Pharmacy Global Health Practice and Research Network's opinion paper: Pillars for global health engagement and key engagement strategies for pharmacists. Issue 6 (5th May 2020) - Crowe, Susie J.; Karwa, Rakhi; Schellhase, Ellen M.; Miller, Monica L.; Abrons, Jeanine P.; Alsharif, Naser Z.; Andrade, Christina; Cope, Rebecca J.; Dornblaser, Emily K.; Hachey, David; Holm, Michelle R.; Jonkman, Lauren; et al.
Abstract: The scope of pharmacy practice in global health has expanded over the past decade creating additional education and training opportunities for students, residents and pharmacists. There has also been a shift from short‐term educational and clinical experiences to more sustainable bidirectional partnerships between high‐income countries (HICs) and low‐ to middle‐income countries (LMICs). As more institutional and individual partnerships between HICs and LMICs begin to form, it is clear that there is a lack of guidance for pharmacists on how to build meaningful, sustainable, and mutually beneficial programs. The aim of this paper is to provide guidance for pharmacists in HICs to make informed decisions on global health partnerships and identify opportunities for engagement in LMICs that yield mutually beneficial collaborations. This paper uses the foundations of global health principles to identify five pillars of global health engagement when developing partnerships: (a) sustainability, (b) shared leadership, (c) mutually beneficial partnerships, (d) local needs‐based care and (e) host‐driven experiential and didactic education. Finally, this paper highlights ways pharmacists can use the pillars as a framework to engage and support health care systems, collaborate with academic institutions, conduct research, and interface with governments to improve health policy.